Expectancies mediate the relationship between perceived injustice and return to work following whiplash injury: A 1‐year prospective study. (11th May 2017) - Carriere, J.S.; Thibault, P.; Adams, H.; Milioto, M.; Ditto, B.; Sullivan, M.J.L.
Abstract: Background: Emerging evidence suggests that perceived injustice is a risk factor for work disability in individuals with whiplash injury. At present, however, little is known about the processes by which perceived injustice impacts on return to work. The purpose of this study was to examine whether expectancies mediated the relationship between perceived injustice and return to work in patients with whiplash injury. Method: One hundred and fifty‐two individuals (81 men, 71 women) with a primary diagnosis of whiplash injury completed self‐report measures of pain intensity, perceived injustice and return‐to‐work expectancies following admission to a rehabilitation programme. Work status was assessed 1 year after discharge. Results: Consistent with previous research, high scores on a measure of perceived injustice were associated with prolonged work disability. Results indicated that high perceptions of injustice were associated with low return‐to‐work expectancies. Causal mediation analyses revealed that expectancies fully mediated the relationship between perceived injustice and return to work. Conclusion: The findings suggest that intervention techniques designed to target expectancies could improve return‐to‐work outcomes in patients with whiplash injury. Discussion addresses the processes by which expectancies might impact on return‐to‐work outcomes and the manner in which negative return‐to‐work expectancies might be modified through intervention. Significance: The study confirms that expectancies are the mechanism through which perceived injustice impacts return to work following whiplash injury. The findings suggest that interventions designed to specifically target return‐to‐work expectancies might improve rehabilitation outcomes in patients with whiplash injury.